Agile Leadership, Digital Transformation and Employee Performance: The Roles of Work Motivation and Job Satisfaction in Public Higher Education - Nurul Badriyah; Dewie Tri Wijayati Wardoyo; Andre Dwijanto Witjaksono (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study examines the relationships among agile leadership, digital transformation, work motivation, job satisfaction and employee performance among administrative and technical staff at Universitas Negeri Surabaya (UNESA). A quantitative cross-sectional design was employed, and data were collected from 248 respondents selected through stratified random sampling across different organizational units. The proposed model was tested using partial least squares structural equation modelling with SmartPLS 4. The findings show that agile leadership has positive and significant effects on digital transformation and work motivation. Digital transformation positively influences work motivation and job satisfaction, while work motivation positively affects job satisfaction and employee performance. Job satisfaction also has a positive effect on employee performance. However, agile leadership does not significantly affect job satisfaction or employee performance, and digital transformation does not significantly affect employee performance. These results indicate that leadership, technological change and employee-related factors have distinct roles in shaping organizational outcomes. In particular, work motivation and job satisfaction emerge as important determinants of employee performance, while agile leadership is more strongly associated with digital transformation and motivation. This study contributes to the literature by providing empirical evidence from a legally autonomous public university undergoing institutional and digital transformation. The findings also offer practical implications for university leaders seeking to strengthen adaptive leadership, improve digital systems and enhance employee motivation, satisfaction and performance.